Insights into the history and trends of nanotechnology for the treatment of hepatocellular carcinoma: a bibliometric-based visual analysis - Yulei Zhao; Xingxin Wang; Xiaoman Yang; Jiaheng Li; Bingbing Han (Discover Oncology)
Abstract Background Nanotechnology has great potential and advantages in the treatment of hepatocellular carcinoma (HCC), but the research trends and future directions are not yet clear. Objectives Analyze the development trajectory, research hotspots, and future trends of nanotechnology and HCC research globally in the past 20 years, providing a more comprehensive and intuitive reference for researchers in this field. Methods Retrieve relevant literature on nanotechnology and HCC research in the Web of Science (WOS) Core Collection database, and conduct bibliometric analysis using software such as CiteSpace, VOSviewer, and SCImago Graphica. Results A total of 852 English publications meeting the criteria were retrieved from the WOS database, with an overall increasing trend in the number of publications and citation frequency over the years. China leads in the number of publications and international collaborations, followed by the USA and India. The most influential research institution is the Chinese Academy of Sciences, the most influential scholar/team is the Rahman, Mahfoozur team, and the journal with the most publications is the International Journal of Nanomedicine. A comprehensive analysis reveals that the current main research directions include new types of nanoparticles, targeted drug delivery systems, photothermal/photodynamic therapy, gene delivery systems, diagnostics, and imaging. It is anticipated that further collaboration among scholars, institutions, and countries will accelerate the development of nanotechnology in the field of HCC research. Conclusion This study provides an in-depth analysis of the research status and development trends of nanotechnology in treating HCC from a bibliometric perspective, offering possible guidance for researchers to explore hot topics and frontiers, select suitable journals, and partners in this field.